(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
The usefulness of machine in industries and other areas of life cannot be overemphasized. This work considers the effect of wears and tears of machines as a result of usage and the value of depreciation with their effect on productivity on the long run of an industrial machine. A consideration of machine whose life depends on the rate of depreciation with time and magnitude of usage in production process has been identified to exhibit some functional expression. The life span of a machine with effect from the date of acquisition in conjunction with its capacity at book value is modeled as a geometric sequence a, ar, ,…, ,... . This model is used to demonstrate some managerial decisions to maintain optimal production from machine usage with less break down time. The practical application of these expressions is illustrated and the method proves effective in machine life management. The method also proves helpful in production control for optimal yield for the industry.